Colombia : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
In this paper, the structure of Colombia's financial sector is analyzed and various risks of the financial sector are studied. Supervision of the financial system can be performed by supervisory architecture, banking supervision, various securities, and insurance policies. Systemic liquidity provision, deposit insurance, and bank resolution form the financial safety net. Finally, financial stability and macroprudential framework have been discussed. Macroprudential tools and policies are also explained in detail.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet